PENERAPAN PBL BERBANTUAN KARTU PERMAINAN TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - Cintya, Yulyta; Nani Kurniati; Eka Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low mathematical critical thinking skills remain a significant challenge in mathematics education. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by game card media on the mathematical critical thinking skills of eighth-grade students at SMPN 3 Mataram on the topic of the Pythagorean Theorem. This research employed a quantitative approach with a quasi-experimental design. The sample was selected using cluster random sampling, consisting of class VIII.2 as the experimental group and class VIII.3 as the control group. Data were collected through posttest instruments measuring four critical thinking indicators: interpretation, analysis, evaluation, and inference. The results showed that the experimental class achieved a higher mean score (73.96) compared to the control class (65.23). Hypothesis testing using the pooled variance t-test yielded tcount = 4.601 > ttable = 2.008, leading to the rejection of H0. Furthermore, an effect size of 1.289 was obtained, categorized as large. These findings conclude that the implementation of the PBL model assisted by game card media significantly affects and provides a strong positive impact on students' mathematical critical thinking skills.